Mental Toughness dan Achievement Goals: Faktor Psikologis Pembentuk Flow State Atlet Beladiri di Jawa Barat - Gilang Arrasyid; Nuram Mubina; R Yuwono Pratomo (EduInovasi: Journal of Basic Educational Studies, 2025)
To meet the demand for high-achieving martial arts athletes in West Java, mental toughness and achievement goals are essential for athletes to achieve optimal performance. This study aims to investigate the influence of mental toughness and achievement goals on the flow state among martial arts athletes in West Java Province. The method used is quantitative with a causal design. The participants consisted of 158 athletes aged between 13 and 35 years, from various martial arts disciplines such as Pencak Silat, Taekwondo, Karate, and others. The data analysis methods used include normality tests, linearity tests, multiple regression analysis, coefficient of determination tests, and categorization tests. All data analyses were conducted using SPSS Statistics version 25.0. The instruments used in this study include the Flow State Scale (FSS), the Mental Toughness Index, and the 2 x 2 Achievement Goals Questionnaire. The regression analysis results show that mental toughness has a significant influence on the flow state, while achievement goals do not have a significant partial effect. However, simultaneously, both variables significantly influence the flow state, with a contribution of 59.8%. These findings emphasize the importance of mental strength and achievement-oriented behavior in shaping the optimal performance conditions of athletes during competition. This study is expected to serve as a foundation for the development of psychological training programs aimed at enhancing the performance of martial arts athletes by strengthening mental toughness and managing achievement goals to produce outstanding athletes.